Workshop Kewirausahaan Berbasis Teknologi Bagi Siswa Sekolah Menengah Kejuruan Ulu Rawas - Deni Apriadi; Alfiarini; Robi Yanto (Yayasan Kajian Riset dan Pengembangan RADISI, 2022)
The development of technology brings business opportunities for young people. 89% of Indonesia's population are Smartphone users, which is equivalent to 167 million people. Based on the current potential, technology-based businesses have enormous opportunities. However, until now, the entrepreneurial spirit of college graduates and vocational school graduates in Indonesia is still weak. Based on the field survey on the SMKN Rawas Ulu, Musi Rawas Utara Regency, we found that most of the students are not familiar with the technopreneurship . The absence of a special topic on it and the lack of information might be causing the lack of understanding and interest in entrepreneurship. We also found that student's knowledge and understanding of technoprenuership increased after a technology-based entrepreneurship workshop was conducted. In addition, students' motivation and mindset changed about technology-based business. This can be seen from the post-test results as much as 57% of students wish to become a technopreneur